Derangements of immunological proteins in HIV-associated diffuse large B-cell lymphoma: the frequency and prognostic impact - Vaughan, Jenifer; Patel, Moosa; Suchard, Melinda; Gededzha, Maemu; Ranchod, Heena; Howard, Wayne; Snyman, Tracy; Wiggill, Tracey (Frontiers in Cellular and Infection Microbiology, 2024)
Diffuse large B-cell lymphoma (DLBCL) is an aggressive malignancy of B-cells frequently encountered among people living with HIV. Immunological abnormalities are common in immunocompetent individuals with DLBCL, and are often associated with poorer outcomes.Currently, data on derangements of immunological proteins, such as cytokines and acute phase reactants, and their impact on outcomes in HIV-associated DLBCL (HIV-DLBCL) is lacking.This study assessed the levels and prognostic relevance of interleukin (IL)-6, IL-10 and Transforming Growth Factor Beta (TGFβ), the acute phase proteins C-reactive protein (CRP) and ferritin; serum free light chains (SFLC) (elevation of which reflects a prolonged pro-Deleted: